Association of Oxidative Stress and Disease Activity in Rheumatoid Arthritis Patients in Babylon Province (Medico Legal Update, 2020)
Background: Several lines of evidence suggest a role for oxidative stress in the pathogenesis of rheumatoidarthritis (RA). Both reactive oxygen species (ROS) and reactive nitrogen species (RNS) damage cartilage.Tissue injury in inflammation results in NO• production by articular chondrocytes and synovial fibroblastsand elevated levels of NO. are observed in the serum and synovial fluid of RA patients. The free radicals,particularly NO•• and O2•?, inhibit the synthesis of matrix components like proteoglycans by chondrocytesand also damage the extracellular matrix through activation and up regulation of matrix metalloproteinases.Aim of the Study: To study the possible association between oxidative stress and RA.Patients and Method: The present case control study was conducted on sixty one patients (18 males and43 females) with RA patients admitted to Rheumatoid Unit in Merjan Teaching Medical City, BabylonProvince, Iraq, duration the period September 2018 to July 2019, as well as 127 apparently healthy controlsubjects (41 males, 86 females) as control group. Malondialdehyde (MDA) and total antioxidant capacity(TAC) using ELISA technique.Results: The level of MDA was higher in patients with RA in comparison with control group, with medianof 2.35 (1.93) versus 0.86 (0.52); the difference was highly significant (P< 0.001). On the other hand, thelevel of TAC was lower in patients with RA in comparison with control subjects, with median of 0.10 (0.21)versus 0.53 (1.02), respectively; the difference was highly significant (P< 0.001).Conclusion: The current study documented that RA is significantly associated increased oxidative stress.